Volatility transmission in emerging European foreign exchange markets - Vít Bubák; Evézen Kocenda; Filip Zikes (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper studies the dynamics of volatility transmission between Central European currencies and euro/dollar foreign exchange using model-free estimates of daily exchange rate volatility based on intraday data. We formulate a flexible yet parsimonious parametric model in which the daily realized volatility of a given exchange rate depends both on its own lags as well as on the lagged realized volatilities of the other exchange rates. We find evidence of statistically significant intra-regional volatility spillovers among the Central European foreign exchange markets. With the exception of the Czech currency, we find no significant spillovers running from euro/dollar to the Central European foreign exchange markets. To measure the overall magnitude and evolution of volatility transmission over time, we construct a dynamic version of the Diebold-Yilmaz volatility spillover index, and show that volatility spillovers tend to increase in periods characterized by market uncertainty.
Keywords: C50; F31; G15; 330; foreign exchange markets; volatility; spillovers; intraday data; nonlinear dynamics; Wechselkurs; Euro; US-Dollar; Volatilität; Spillover-Effekt; Internationaler Preiszusammenhang; Devisenmarkt; Aufstrebende Märkte; Ostmitteleuropa